The shape of gold - Bally, Benjamin; Giacalone, Giuliano; Bender, Michael (The European physical journal. A, Hadrons and nuclei, 2023)
Having a detailed theoretical knowledge of the low-energy structure of the heavy odd-mass nucleus 197Au is of prime interest as the structure of this isotope represents an important input to theoretical simulations of collider experiments involving gold ions performed at relativistic energies. In the present article, therefore, we report on new results on the structure of 197Au obtained from state-of-the-art multi-reference energy density functional (MR-EDF) calculations. Our MR-EDF calculations were realized using the Skyrme-type pseudo-potential SLyMR1, and include beyond mean-field correlations through the mixing, in the spirit of the Generator Coordinate Method (GCM), of particle-number and angular-momentum projected triaxially deformed Bogoliubov quasi-particle states. Comparison with experimental data shows that the model gives a reasonable description of 197Au with in particular a good agreement for most of the spectroscopic properties of the 3/2+1 ground state. From the collective wave function of the correlated state, we compute an average deformation β¯(3/2+1)=0.13 and γ¯(3/2+1)=40∘ for the ground state. We use this result to construct an intrinsic shape of 197Au representing a microscopically-motivated input for precision simulations of the associated collider processes. We discuss, in particular, how the triaxiality of this nucleus is expected to impact 197Au+197Au collision experiments at ultrarelativistic energy.
Gesehen am 05.06.2023